A Novel Androgen-Induced lncRNA FAM83H-AS1 Promotes Prostate Cancer Progression via the miR-15a/CCNE2 Axis - Liu, Bo; Qian, Duocheng; Zhou, Weidong; Jiang, Huiyang; Xiang, Zhendong; Wu, Denglong (Frontiers in Oncology, 2021)
Abstract Prostate cancer (PCa) is one of the most common types of cancer among men worldwide. However, the roles of lncRNAs in PCa remained to be unclear. This study showed that lncRNA FAM83H-AS1 was up-regulated in Prostate adenocarcinoma (PRAD), Bladder Urothelial Carcinoma (BLAC), and Kidney renal papillary cell carcinoma (KIRP) samples. AR signaling played the most important role in PCa tumorigenesis and development. In this study, the results validated that AR signaling was involved in up-regulating FAM83H-AS1 expression in PCa cell. Loss-of-functions assays demonstrated that FAM83H-AS1 acted as an oncogene in PCa by modulating cell proliferation, cell cycle, and migration. Bioinformatics analysis revealed that FAM83H-AS1 was remarakably related to the regulation of cell cycle and DNA replication through affecting multiple regulators related to these pathways, such as CCNE2. Mechanically, we found that FAM83H-AS1 played its roles though sponging miR-15a to promote CCNE2 expression. These findings indicated that FAM83H-AS1 is a novel diagnostic and therapeutic marker for PCa.